O papel do dialeto no desempenho de alunos na prova de proficiência Deutsches Sprachdiplom I - Messa, Rosângela Markmann (Contingentia, 2008)
This paper investigates the role of Hunsrückisch, a dialect spoken by German descendents in South Brazil, in regard to the performance of high school students in the proficiency exam Deutsches Sprachdiplom (DSD-I). The article will first discuss the concept of bilinguism and then analyzes the performance of bilingual students (Portuguese/German) from the Instituo de Educação Ivoti in DSD-I exams over the last 5 years.